PRINCIPAL DEVELOPMENT OF CERTIFIED TEACHERS TO ENHANCE THE QUALITY OF LEARNING IN BABAHROT DISTRICT ELEMENTARY SCHOOLS, SOUTHWEST ACEH REGENCY - Irfandri; Khairuddin; Bahrun (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Certified teacher development is assistance or a series of efforts carried out by school principals towards certified teachers in conducting professional competence improvement to enhance the quality of education. The purpose of this research is to determine the implementation of principal's coaching for certified teachers in improving the quality of education, including: planning; implementation; follow-up, and obstacles. This research was conducted qualitatively with a case study research design. Data collection techniques included interviews, observations, and documentation. Data validity checking techniques included more thorough observations and triangulation testing. Subjects in this study were school principals and certified teachers. The findings of the research are as follows: (1) Academic supervision planning begins at the beginning of the academic year with a work meeting involving the school principal and certified teachers. The coaching program includes supervision, training, and technical guidance. The coaching focus includes: lesson plan supervision, RPP monitoring, learning process, and assessment of learning outcomes; training to improve teachers' competencies in IT; (2) Implementation is carried out with coaching approaches conducted directly and indirectly. The coaching pattern is divided into two, namely academic and non-academic. The academic coaching pattern includes two activities, namely classroom visits and observations, while the non-academic coaching pattern is carried out through personal guidance and group guidance; (3) Follow-up in coaching uses coaching techniques in individual coaching activities as a follow-up to academic supervision activities, with the aim of making teachers aware of their potential so that they realize that their weaknesses can be maximized through their own potential; (4) Principal's time constraints in coaching activities due to heavy workloads, limited certified teachers' competencies in IT, frequent changes of school principals, inadequate facilities and infrastructure, and limited BOSP fund budgets in conducting training and technical guidance.